Euro-Par 2021: Parallel Processing : 27th International Conference on Parallel and Distributed Computing, Lisbon, Portugal, September 1-3, 2021, Proceedings - International EURO-PAR Conference; Sousa, Leonel; Roma, Nuno; Tomás, Pedro (Lecture Notes in Computer Science, 2021)
This book constitutes the proceedings of the 27th International Conference on Parallel and Distributed Computing, Euro-Par 2021, held in Lisbon, Portugal, in August 2021. The conference was held virtually due to the COVID-19 pandemic.The 38 full papers presented in this volume were carefully reviewed and selected from 136 submissions. They deal with parallel and distributed computing in general, focusing on compilers, tools and environments; performance and power modeling, prediction and evaluation; scheduling and load balancing; data management, analytics and machine learning; cluster, cloud and edge computing; theory and algorithms for parallel and distributed processing; parallel and distributed programming, interfaces, and languages; parallel numerical methods and applications; and high performance architecture and accelerators.